2015
DOI: 10.1177/0394632015572745
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and functions of stanniocalcins in cancer

Abstract: Corpuscles of stannius (CS), a small endocrine gland located on the ventral surface of the kidneys of bony fishes, is extracted to purify stanniocalcins (STCs), which inhibit whole-body Ca2+ influx in the whole body, especially in gill and gut. CSs were first considered to be unique endocrine glands in fish, but were further verified to appear in mammalians, indicating that STCs may function in mammalians as calcium regulation, oxidative stress, anti-inflammation, angiogenesis, ischemia reperfusion, etc. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The stanniocalcin (STC) family consists of two proteins, STC1 and STC2, which are expressed in various human tissues 16 , such as pancreas, spleen, kidney, and skeletal muscle. Numerous studies have examined STC1 and STC2 in the tumor microenvironment, where they have positive effects on tumor migration and invasion 17 , 18 . Clinically, STC2 has been proposed to be a biomarker for various cancers, in association with the formation of tumor neovascularization 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The stanniocalcin (STC) family consists of two proteins, STC1 and STC2, which are expressed in various human tissues 16 , such as pancreas, spleen, kidney, and skeletal muscle. Numerous studies have examined STC1 and STC2 in the tumor microenvironment, where they have positive effects on tumor migration and invasion 17 , 18 . Clinically, STC2 has been proposed to be a biomarker for various cancers, in association with the formation of tumor neovascularization 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of STC2 expression within the tumor microenvironment found that STC2 enhanced tumor cell migration and invasion [42,43]. Clinical studies con rmed STC2 as a new biomarker of multiple cancers due to its involvement in tumor neovascularization [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the glycoprotein STC2 was overexpressed as well. The glycoprotein is involved in the homeostasis of calcium and phosphate (57). STC2 has been reported to be upregulated in E2-treated MCF-7 cells (58), breast cancer (59) and is associated with proliferation in cancer (60,61).…”
Section: -Esr1 Cells Mcf-7 Cells Treatment Duration --------------mentioning
confidence: 99%